Maternal And Neonatal Program And Effective Spending Improves Health In A Hospital In Peru - Neciosup Montenegro, Lourdes del Rocio (2024)
Budget programs are implemented in response to previously identified and defined problems; Therefore, the Ministry of Health carries out the maternal and neonatal program, planning a structured strategy, based on available evidence in critical points of maternal and newborn sexual and reproductive health; Likewise, the need to direct budgetary resources, improving the efficiency and effectiveness of spending that impact program activities, reducing complications of pregnancy, childbirth and puerperium; being the objective to propose the Friendly Model of the maternal and neonatal program for the effective execution of public expenditure in a hospital in Piura-2023. A quantitative, applied, non-experimental, descriptive-exploratory, cross-sectional and purposeful methodology was used, recruiting a census sample of 80 health workers, applying the survey technique, using a correlational inferential descriptive statistic of the study variables, taking results in relation to the perception of the program at the middle level linked to its dimensions and, for the variable public expenditure in nexus with its dimensions of efficiency and effectiveness, also the correlation between the maternal and neonatal pro[1]gram and public expenditure was significant positive moderate (Rho Spearman 0.581); It was concluded that there is moderate positive agreement between the maternal and neonatal programme and public expenditure, in addition to the clear need to proceed with the development of a training and intervention plan, based on human rights, with an intercultural approach, improving assistance to the health services of this institution for the benefit of the population.